Kinin B1 receptor antagonism is equally efficient as angiotensin receptor 1 antagonism in reducing renal fibrosis in experimental obstructive nephropathy, but is not additive - Huart, Antoine; Klein, Julie; Gonzalez, Julien; Buffin-Meyer, Bénédicte; Neau, Eric; Delage, Christine; Calise, Denis; Ribes, David; Schanstra, Joost P.; Bascands, Jean-Loup (Frontiers in Pharmacology, 2015)
Background: Renal tubulointerstitial fibrosis is the pathological hallmark of chronic kidney disease (CKD). Currently, inhibitors of the renin–angiotensin system (RAS) remain the sole therapy in human displaying antifibrotic properties. Further antifibrotic molecules are needed. We have recently reported that the delayed blockade of the bradykinin B1 receptor (B1R) reduced the development of fibrosis in two animal models of renal fibrosis. The usefulness of new drugs also resides in outperforming the gold standards and eventually being additive or complementary to existing therapies. Methods: In this study we compared the efficacy of a B1R antagonist (B1Ra) with that of an angiotensin type 1 receptor antagonist (AT1a) in the unilateral ureteral obstruction (UUO) model of renal fibrosis and determined whether bi-therapy presented higher efficacy than any of the drugs alone. Results: B1R antagonism was as efficient as the gold-standard AT1a treatment. However, bitherapy did not improve the antifibrotic effects at the protein level. We sought for the reason of the absence of this additive effect by studying the expression of a panel of genes involved in the fibrotic process. Interestingly, at the molecular level the different drugs targeted different players of fibrosis that, however, in this severe model did not result in improved reduction of fibrosis at the protein level. Conclusions: As the B1R is induced specifically in the diseased organ and thus potentially displays low side effects it might be an interesting alternative in cases of poor tolerability to RAS inhibitors.